EKSTRAK DAUN PANDAN WANGI (PANDANUS AMARYLLIFOLIUS ROXB.) DALAM MENGENDALIKAN ULAT GRAYAK (SPODOPTERA LITURA F.) DI LABORATORIUM - Benauli, Arkhiadi; Sitohang, Nurdin; Gusriani, Yunda; Harefa, Syukur Berkat (LPPM Universitas Katolik Santo Thomas Medan, 2023)
This research was conducted at the Biology Laboratory, Faculty of Agriculture, Universitas Katolik Santo Thomas, Medan. This study aims to determine the potential of fragrant pandan leaf extract as a vegetable pesticide in controlling armyworm pests. This study used a non-factorial completely randomized design (CRD). The treatment factor was fragrant pandan leaf extract (Pw) which consisted of 5 treatments and 4 replications, namely: Pw0 = (control/without giving fragrant pandan leaf extract), Pw1 = 20 ml of fragrant pandan leaf extract, Pw2 = 40 ml of pandan leaf extract fragrant, Pw3 = 60 ml of fragrant pandan leaf extract and Pw4 = 80 ml of fragrant pandan leaf extract, each treatment added with 100 ml of distilled water. The results showed that the highest percentage of mortality (100%) at 108 hours after application (JSA) was found in the treatment of 80 ml of fragrant pandan leaf extract + 100 ml of aquadest. The fastest death time of 50% of armyworms was found in the treatment of 80 ml of fragrant pandan leaf extract + 100 ml of aquadest, which was 30 JSA.